Using indicators as a catalyst for inclusive education in the Pacific Islands. Issue 7 (3rd July 2017) - Sharma, Umesh; Forlin, Chris; Marella, Manjula; Jitoko, Filipe
ABSTRACT: The Pacific Island countries are committed to promoting disability-inclusive education through enactment of the Pacific Education Development Framework. To support this move, key stakeholders have identified the need for developing local and contextually appropriate indicators for measuring progress of disability-inclusive education. This paper reports on the usefulness of a newly developed tool (Pacific Indicators for Disability-Inclusive Education – Pacific-INDIE) as a catalyst in implementing inclusive education in the Pacific. Data were collected from a range of stakeholders who have used the Pacific-INDIE in three countries (Fiji, Samoa and Solomon Islands). Thematic analysis was used to identify the key themes relating to the usefulness of the tool. The key themes that emerged from the data included, positive outcomes, challenges, planned future directions, and process issues. The findings discussed are related to how the indicators can best support future policy development and implementation of disability-inclusive education across the region.